The physics of medical imaging [ - Chua, Eu-Hua; Egan, Tim , 1957-; Swain, Tiki; Video Education America (White Plains, N.Y. : VEA (Video Education America), 2009)
"Technological advances developed from our understanding of the electromagnetic spectrum, has provided medical technologists sophisticated tools with which to analyze and interpret bodily process for diagnostic purposes.These methods are usually non-invasive processes for identifying and monitoring diseases or injuries of the body by using images representing internal anatomical structures and organs of the body. "--Container
1. Introduction -- 2. Ultrasound -- 3. Electromagnetic waves -- 4. Radioactivity -- 5. Electromagnetism -- 6. Conclusion
"This program is recorded on DVD-R and may not be compatible with all DVD players"--Container
Director : Tim Egan, Writter : Tiki Swain, Voice over : Adam Mattiliano, Director of photography : Tim Egan, Sound : Simon Brock, Offline editor : Tim Egan, Online editor : Daniel Cowan, Audio post : Daniel Cowan, DVD Producer : Roxxy Fahmy, Production manager : Edwina Baden-Powell, Educational consultants : Ian Walter, John Nicholson, Commissioning editor : Sven Shepherd, Script producer : Kat Rutigliano, Senior producer : Pru Burns, Producer : Eu-Hua Chua, Executive producer : Simon Garner
DVD
English
Keywords: Diagnostic imaging; Educational videos; Medical physics; Radiology, Medical